2011
DOI: 10.1016/j.jesp.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Naturals and strivers: Preferences and beliefs about sources of achievement

Abstract: a b s t r a c tTo understand how talent and achievement are perceived, three experiments compared the assessments of "naturals" and "strivers." Professional musicians learned about two pianists, equal in achievement but who varied in the source of achievement: the "natural" with early evidence of high innate ability, versus the "striver" with early evidence of high motivation and perseverance (Experiment 1). Although musicians reported the strong belief that strivers will achieve over naturals, their preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 21 publications
4
81
1
Order By: Relevance
“…The personnel selection literature and the social psychology literature-beyond the scope of the present article, but nevertheless useful-show that talent definitions and measurements are subjective by nature due to the influence of assessor and assessee personal characteristics (Tormala, Jia & Norton, 2012;Tsay & Banaji, 2011;Vaughan & Hogg, 2005).…”
Section: Inserting Assessors and Assessees Into The Equationmentioning
confidence: 91%
“…The personnel selection literature and the social psychology literature-beyond the scope of the present article, but nevertheless useful-show that talent definitions and measurements are subjective by nature due to the influence of assessor and assessee personal characteristics (Tormala, Jia & Norton, 2012;Tsay & Banaji, 2011;Vaughan & Hogg, 2005).…”
Section: Inserting Assessors and Assessees Into The Equationmentioning
confidence: 91%
“…of the 'high potential' label) on ratees. Important recent findings include a generalized preference for potential (i.e., a phenomenon whereby raters consistently rate people with high potential in a certain domain more positively than people who have already demonstrated good performance in that same domain; see Tormola, Jia & Norton, 2012); naturalness bias (i.e., the tendency to rank innate over acquired sources of performance; see Tsay & Banaji, 2011); and incremental induction (i.e., experimental interventions that can alter a rater's mindset so that he or she demonstrates less naturalness bias; see Heslin, Latham & Vandewalle, 2005).…”
Section: Identification Of Relevant Theoretical Perspectives On Talentmentioning
confidence: 99%
“…Although this latter perspective seems particularly attractive considering the changing demand-supply dynamics in the labor market (cf. the discussion on 'making or buying' talent), research has shown that most organizational decision makers tend to believe that talent is, for the largest part, inborn (e.g., Tsay & Banaji, 2011).…”
Section: Tensions In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Social psychology "operationalizes talent as the perception of talent", and focuses on different issues including decision-making and mindsets (Dries, 2013b, p. 278). As depicted in the work done by Dries (2013b), research on social psychology comprises studies on generalised preference for potential (e.g., Tormola, Jia & Norton, 2012), naturalness bias (e.g., Tsay & Banaji, 2011) and incremental induction (e.g., Heslin, Latham, & Vandewalle, 2005). Recent studies suggest that the cognitive psychology discipline should be considered as a "further source of potential understanding about talent management decisions" (Boudreau, 2013, p. 287).…”
Section: Cognition Within Talent Managementmentioning
confidence: 99%